Synthesis and Characterization of Ni-WO3/Sulfated Zirconia Nano catalyst for Isomerization of N-Hexane and Iraqi Light Naphtha - Kamel, Safa Abdul Salam; Mohammed, Wadood Taher; Aljendeel, Haider (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
This work deals with preparation of Sulfated Zirconia catalyst (SZ) for isomerization of n-hexane model and refinery light naphtha, as well as enhanced the role of promoters to get the target with the mild condition, stability, and to prevent formation of coke precursors on strong acidic sites of the catalyst. The prepared SZ catalysts were characterization by fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Brunauer –Emmett-Teller (BET) surface area analysis, Thermogravimetric Analysis (TGA), Scanning Electron Microscope (SEM) and atomic force microscopy (AFM) Analyzer. The results illustrate that the maximum conversion and selectivity for n-hexane isomerization with Ni-WSZ and operating temperature of 150 °C was 80.1%  and 96 %   respectively .Other set of experimental with light naphtha , the results show that the maximum conversion and selectivity with Ni-WSZ and operating temperature of 150 °C  was 73.6%   and  74%   respectively.